Pengembangan Sistem Informasi Perjalanan Kapal dalam Satu Voyage pada PT. Lima Sekawan Marine Grup berbasis Website - Muhammad Faris Faishal; Adam Hendra Brata; Eriq Muhammad Adams Jonemaro (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Lima Sekawan Marine Group is a National Shipping company that conducts planning activities by analyzing and evaluating ship trips from one port to another. During the planning process to evaluate ship trips in a comparison between data trip planning and trip reports, it is still done manually, using Excel. In manual data management, these are several problems namely, data is difficult to read, data is not quickly updated, and data is poorly stored properly. Required for several divisions that require analyzing the data, data is more quickly accepted. Therefore PT. Lima Sekawan Marine Grup needs to optimize the management of travel data analysis in one voyage with a website-based ship travel information system. This information system was built to assist operational divisions in carrying out boat trip planning (trip planning) and ship trip reporting (trip reporting). Then it can help other divisions in obtaining ship evaluation data, complete and accurate. This system can also assist in the process of ordering ships or shipping charters. This web-based information system, in its implementation, uses the MVC (Model View Controller) pattern. In this study, testing was divided into unit testing, validation testing, and compatibility testing.